Killing the angel in the house and “telling the truth about my own experiences as a body”: an Islamic perspective on Virginia Woolf’s stance on Victorian gender ideology - Hasan, Md. Mahmudul (2016)
In English literary studies, Virginia Woolf (1882-1941) is widely regarded as the female Shakespeare of our time. Some even believe that she has surpassed William Shakespeare (1564-1616) as the most widely discussed author in current literary discourse. The overarching influence of second-wave feminist thinking on contemporary gender studies and the spearheading of sexual revolution and other related radical ideas in Woolf’s writings have contributed to her becoming an icon of the women’s rights movement. One of her most prominent concerns is her rejection of Victorian gender ideology. In her “Professions for Women” (1931), she flouts the Victorian domestic-angel model of womanhood and summarily disregards the feminine attributes of conventional gender roles in their totality. In doing so, she discourages women’s spirits of devotion, self-sacrifice and self-denial in family life. What is more, she straightaway rejects the need for women to remain chaste and sexually pure in marital relationship. As regards women’s literary practices, she promotes limitless freedom to represent intimate experiences and produce sexually explicit materials, and thus she aligns herself more closely with the position of anti-censorship feminists. While Islam rejects any sexual double standard in gender norms, it does not discount the need for men or women to maintain commonly accepted socio-cultural values essential for keeping the institution of family well-integrated and more humane. Nor does it allow irresponsible exercise of freedom of expression, especially when it concerns producing literature verging on erotica and pornography. Based on these observations, in my paper, I will look at Woolf’s rejection of Victorian gender ideology from an Islamic perspective.